#TITLE_ALTERNATIVE# - (NIM: 15312052), IRSYAD
The excessive concentration of gas pollutant of sulphur dioxide (SO2) in ambient air may cause adverse impacts on health and the environment. Monitoring of ambient air is needed in order to evaluate the air quality. The results of air monitoring depends on two key roles i.e. sampling and analysis methods.monitoring of ambient air with passive sampler can be an alternative option to be applied in the measurement of the concentration of sulfur dioxide (SO2). This research used badge passive sampler because of several advantages such as a high tolerance for a long exposure time, high sensivity in the analysis and not affected by fluctuations in concentration. The results of air pollution monitoring with passive method allows for mapping of the distribution of pollutant concentrations in a wide area. This study analyzed the spatial variation of SO2 pollutant concentrations in the 19 cities and counties in West Java with each of the two measurement points. The primary point of measurement carried out in the residential neighborhoods while the secondary is an alternative point of the area of transportation, industrial, and commercial to determine the distribution of SO2 in ambient air pollutants. Meteorological factors such as wind direction and speed, temperature and pressure, as well as moisture were minimised with the modification and the use of shelter for sampling protection. Laboratory analysis method from the results of air sampling is done by ion chromatography. The reading of the concentration from ion chromatography is in the form of sulphate (SO4 2-) anion. Precision measurements of SO2 with passive badge sampler was of 75,39% and still meet the acceptance criterion from NIOSH for RSD value of 25%. The limit of detection for ion chromatography analysis methods and the overall method of passive sampling are 0,2607 μg/m3 and 1,3849 μg/m3, respectively.